Pengaruh Self Efficacy, dan Komitmen Organisasi Terhadap Kinerja Pegawai (PNS) Pegawai Negeri Sipil: Pada Dinas Kesehatan Kabupaten Tabanan - Laksmi, Ni Putu Desi Paramitha; Kawiana, I Gede Putu; Yayati W., Ida I Dewa Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The good performance of the Tabanan District Health Office is also supported by the organizational commitment formed in it. By showing good performance, employees will feel satisfied with the results of their work. This satisfaction forms a strong organizational commitment within the Tabanan District Health Office. The purpose of this study is to determine the effect of self-efficacy and organizational commitment on employee performance. The research method used in this study is multiple linear regression analysis. The sample used in this study were 67 respondents, namely employees of the Tabanan District Health Office. The data analysis techniques used in this study are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study, it can be seen that: (1) Self efficacy has a positive and significant effect on employee performance. (2) Organizational commitment has a positive and significant impact on employee performance. (3) Simultaneously self-efficacy and organizational commitment have a positive and significant impact on employee performance at the Tabanan District Health Office. The magnitude of the influence of independent variables on employee performance is 85.5%.